مقاربة سوسيولوجية لظاهرة اعتناق الإسلام في الدول الغربية - بوالفلفل، إبراهيم (جامعة محمد الصديق بن يحيى جيجل, 2018)
The aim of this paper is to investigate the reality of conversion to Islam in Western countries. These societies have known a steady increase in the proportions of new Muslims. We will try to highlighting reasons and motives behind this increase, we will also seek through this study to draw a profile for the persons who convert to Islam and shed light on Islamic religion's characteristics which attract Westerners, and motivate them to embrace Islam, and the reasons for involving in extremism and violence for some of them.
تهدف هذه الورقة العلمية إلى تقصي واقع اعتناق الإسلام في الدول الغربية حيث عرفت هذه المجتمعات تزايدا مضطردا في نسب المسلمين الجدد أو الوافدين الجدد على اعتناق الدين الإسلامي من هنا سنحاول قراءة بعض الأسباب والدوافع الكامنة وراء هذا التزايد وكذا سنسعى من خلال هذه الدراسة إلى رسم ملمح للفئات الأكثر إقبالا على الدين الإسلامي وإلقاء الضوء على بعض خصائص الدين الإسلامي التي ينجذب من خلالها الغربيون وتدفعهم إلى ترك دينهم واعتناق الإسلام، وأسباب انزلاق بعضهم إلى التطرف والعنف.
Keywords: التنشئة الاجتماعية -- المعتقدات الدينية -- اعتناق الإسلام -- الفكر الغربي